Ontology based Intelligent System for Online Employer Demand Analysis - Terblanche, C.; Wongthongtham, P.; Vilazon-Terrazas, B.; Wongthongtham, Pornpit (IGI Global, 2016)
Identifying employer demand is crucial for a nation to ensure it develops accurate and reliable education, workforce development and immigration policies. Skills shortages globally pose a real and urgent need for proper investigation and workforce development planning into the future. Analysing workforce development and employer demand needs through online job market allows much deeper and wider research into skill shortages. Current methods do not provide the level of depth required to address such important economic implications. In this chapter, the authors present an intelligent system aiming to gather and analyse current employer demand information from online job advertisements. An Employer Demand Ontology has been developed and to further the ontology functionality, the Employer Demand Identification Tool has been developed as a semi-automated means to gather and analyse current employer demand information on a regular basis.